2021
DOI: 10.33084/jmd.v1i1.2264
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Studies of Phytoconstituents Identified in Traditional Siddha Polyherbal Formulations Against Possible Targets of SARS-CoV-2

Abstract: The Indian Traditional Medicines System has long used Siddha polyherbal formulations for different viral diseases. The ingredients of these formulas have been proven to be antiviral. The study focuses on in silico computational evaluation of phytoconstituents of the official Siddha formulation Kabasura, Thonthasura, and Vishasura Kudineer, which were widely used in treating viral fever and respiratory infections and may influence the current SARS-CoV-2 coronary virus pandemic. Maestro interface (Schrödinger Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In addition to its anti-inflammatory effects, in silico studies by Selvaraj et al and Taherkhani et al explored rutin's ability to bind to various metalloproteinases, including gelatinase A (MMP-2), stromelysin (MMP-3), collagenase (MMP-9), metalloelastase (MMP-12), collagenase-3 (MMP-13), and collagenase-2 (MMP-8) [116][117][118]. Rutin has demonstrated potential inhibition of MMP-2 and MMP-9 consistent with findings by Chen et al, who observed reduced MMP-2 and MMP-9 levels in a diabetic wound animal model upon rutin treatment [111].…”
Section: Rutinmentioning
confidence: 99%
“…In addition to its anti-inflammatory effects, in silico studies by Selvaraj et al and Taherkhani et al explored rutin's ability to bind to various metalloproteinases, including gelatinase A (MMP-2), stromelysin (MMP-3), collagenase (MMP-9), metalloelastase (MMP-12), collagenase-3 (MMP-13), and collagenase-2 (MMP-8) [116][117][118]. Rutin has demonstrated potential inhibition of MMP-2 and MMP-9 consistent with findings by Chen et al, who observed reduced MMP-2 and MMP-9 levels in a diabetic wound animal model upon rutin treatment [111].…”
Section: Rutinmentioning
confidence: 99%